Development of a clinically validated in vitro functional assay to assess pathogenicity of novel GAA variants in patients with Pompe disease identified via newborn screening - Goomber, Shelly; Huggins, Erin; Rehder, Catherine W.; Cohen, Jennifer L.; Bali, Deeksha S.; Kishnani, Priya S. (Frontiers in Genetics, 2022)
Purpose: The addition of Pompe disease (Glycogen Storage Disease Type II) to the Recommended Uniform Screening Panel in the United States has led to an increase in the number of variants of uncertain significance (VUS) and novel variants identified in the GAA gene. This presents a diagnostic challenge, especially in the setting of late-onset Pompe disease when symptoms are rarely apparent at birth. There is an unmet need for validated functional studies to aid in classification of GAA variants. Methods: We developed an in vitro mammalian cell expression and functional analysis system based on guidelines established by the Clinical Genome Resource (ClinGen) Sequence Variant Interpretation Working Group for PS3/BS3. We validated the assay with 12 control variants and subsequently analyzed eight VUS or novel variants in GAA identified in patients with a positive newborn screen for Pompe disease without phenotypic evidence of infantile-onset disease. Results: The control variants were analyzed in our expression system and an activity range was established. The pathogenic controls had GAA activity between 0% and 11% of normal. The benign or likely benign controls had an activity range of 54%–100%. The pseudodeficiency variant had activity of 17%. These ranges were then applied to the variants selected for functional studies. Using the threshold of <11%, we were able to apply PS3_ supporting to classify two variants as likely pathogenic (c.316C > T and c.1103G > A) and provide further evidence to support the classification of likely pathogenic for two variants (c.1721T > C and c.1048G > A). One variant (c.1123C > T) was able to be reclassified based on other supporting evidence. We were unable to reclassify three variants (c.664G > A, c.2450A > G, and c.1378G > A) due to insufficient or conflicting evidence. Conclusion: We investigated eight GAA variants as proof of concept using our validated and reproducible in vitro expression and functional analysis system. While additional work is needed to further refine our system with additional controls and different variant types in order to apply the PS3/BS3 criteria at a higher level, this tool can be utilized for variant classification to meet the growing need for novel GAA variant classification in the era of newborn screening for Pompe disease.